Simultaneous adsorption of selected endocrine-disrupting compounds at trace level of concentration by using novel calcium-based metal-organic framework - Sukatis, Fahren Fazzer; Razak, Muhammad Raznisyafiq; Looi, Ley Juen; Lim, Hong Ngee; Abdul Rahman, Mohd Basyaruddin; Aris, Ahmad Zaharin (Elsevier, 2024)
The existence of newly identified water contaminants, such as endocrine-disrupting substances (EDCs), in polluted water sources represents substantial environmental and health concerns. Over novel mixed-linker porous calcium-based metal-organic frameworks (Ca-MIX), the simultaneous adsorptive removal of 17-ethynylestradiol (EE2), perfluorooctanoic acid (PFOA), and bisphenol A (BPA) from aqueous solutions has been studied in terms of adsorption kinetics, adsorption isotherms, and water chemistry effects. The adsorption isotherm and kinetics fit the Langmuir model well and followed pseudo-second-order kinetics. Generally, all three compounds adsorb over Ca-MIX depending on the chemical properties of both the adsorbate–adsorbent and water matrix chemistry. Electrostatic and hydrophobic interactions may explain the adsorption mechanism between EDCs and Ca-MIX. The order from the best to worst removal efficiency was EE2 > PFOA > BPA when Ca-MIX was used as the adsorbent. In conclusion, it can be suggested that this material could be used as an adsorbent capable of removing harmful emerging contaminants in water at trace exposure levels. © 2024